CLASSROOM ACTION RESEARCH AS A SOLUTION FOR THE PROBLEMS AT ISLAMIC RELIGIOUS EDUCATION STUDY IN CLASSROOMS - Musyaffa Rafiqie; Munif Shaleh; Heru Puji Winarso (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
Each teacher is required to be able to carry out Classroom Action Research activities. The teacher's ability to carry out Classroom Action Research activities is a measure of the teacher's success in the process of improving classroom learning. On the other hand, to fulfill teacher competence, in carrying out duties as an educator. Classroom Action Research is one of the research activities to solve problems in Islamic Religious Education (PAI) learning materials. Islamic Religious Education (PAI) learning materials include Aqidah-Akhlaq, AlQur'an and Hadis, Fiqh, History of Islamic Culture, and Arabic.